Pengaruh Penggunaan Media Belajar Multiply Card terhadap Hasil Belajar Materi Perkalian pada Siswa Kelas III SDN Kejayan 1 Pujer Bondowoso - Dewi Sri Puji Lestari (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jember, 2024)
Media that meets good criteria includes those made from easily obtainable or self-made materials. There are several educational media that are very interesting for optimizing the teaching and learning process. One of them is the "multiply card" learning media. The aim of this study is to determine whether there is an effect of using multiply card learning media on the learning outcomes of multiplication material for third-grade students at SDN Kejayan 1 Pujer Bondowoso. The type of research used is quantitative research with a quasi-experimental design with a non-equivalent control group pattern. The subjects in this study were the third-grade students A and B at SDN Kejayan 1 Bondowoso, each consisting of 31 students. The data collection methods used were interviews, observations, and student learning outcome tests. The data analysis techniques used are the independent sample ttest and relative effectiveness test. The result is a t-value of 4.986, which is greater than the table value of 2.000, with an effectiveness score of 57,8%. Based on these results, it can be concluded that there is an effect of using the multiply card learning media on the learning outcomes of multiplication material for third-grade students at SDN Kejayan 1 Pujer Bondowoso.
Reuploud file repositori 15 Apr 2026_Firli_Tata
Keywords: Multiply Card Model; Multiplication; Learning Outcomes.